PEMURNIAN MINYAK JELANTAH (WASTE COOKING OIL) DI KOTA TERNATE MENGGUNAKAN ADSORBEN KULIT PISANG MULU BEBEK (Musa sp) KHAS MALUKU UTARA - Fadlan Muin; Sudir Umar; Abdul Rasid Saraha; Ahmad Muchsin Jayali; Merlin - (Universitas Khairun, 2022)
Cooking oil is a basic need for everyday people, approximately 80% of the people of Ternate City use cooking oil repeatedly for cooking in order to save costs. The repeated use of used cooking oil or waste cooking oil with high heating produces free fatty acids, carbonyl compounds, peroxides, decreases the value and nutrition of fried foods, so that over time it has an impact on health. Efforts to process used cooking oil in the City of Ternate by saving costs but not endangering health really need to be carried out by using the typical North Maluku banana peel (Musa sp) as a natural adsorbent to purify used cooking oil. Starting from the preparation of tools and materials, the processing of banana peels, mixing the ingredients in the adsorbent, testing the levels of free fatty acids, determining the levels of free fatty acids and the characteristics of the clusters of banana peels using the Fourier Transform-Infra Red. In this study, the percentage reduction in free fatty acid levels was 0.833%, which was originally 1.882%. These results indicate that the refining of used cooking oil using banana peels is close to the Free Fatty Acid (FFA) value regulated in the Indonesian National Standard (SNI) of 0.3%. Keywords: Used cooking oil, peel of banana's mouth duck (Musa sp), refining.